The Finnish payroll tax cut experiment revisited, or where did the money go? - Ossi Korkeamäki (European Regional Science Association (ERSA), 2011)
In this paper I evaluate the effects of a regional experiment that reduced payroll-taxes by 3-6 percentage points of the firm's wage sum in Northern and Eastern Finland. I estimate the effect of the payroll-tax reduction on firms' employment, wage sum and profits, and on workers hourly pay and monthly hours worked, by comparing employment and wage changes before and after the start of the experiment to a control region. According to my results, the reduction in the payroll-taxes did not lead to any clear cut aggregate effects in the target region.
Keywords: 330